2004
DOI: 10.1111/j.1464-410x.2004.05014.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of circumcision on urinary tract infection after successful antireflux surgery

Abstract: OBJECTIVETo evaluate whether circumcision during antireflux surgery can reduce the incidence of urinary tract infection (UTI) after successful ureteric reimplantation in patients with primary vesico‐ureteric reflux (VUR).PATIENTS AND METHODSChildren who had undergone antireflux surgery for primary VUR were divided into group 1 (27, circumcised at the time of antireflux surgery at the parents’ request) and group 2 (50, those not circumcised). All antireflux operations were by the Cohen method. Regular urine sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Castellsague et al restricted the absolute indication for circumcision to phimosis secondary to balanitis xerotica obliterans and recurrent balanoposthitis, and elucidated the relative indication of urological abnormalities [16]. Kwak et al demonstrated that circumcision after antireflux surgery in long-term follow up has no significant effect on the number of episodes of postoperative UTI, so they didn't recommend circumcision even in children with vesicoureteral reflux [17].…”
Section: Discussionmentioning
confidence: 98%
“…Castellsague et al restricted the absolute indication for circumcision to phimosis secondary to balanitis xerotica obliterans and recurrent balanoposthitis, and elucidated the relative indication of urological abnormalities [16]. Kwak et al demonstrated that circumcision after antireflux surgery in long-term follow up has no significant effect on the number of episodes of postoperative UTI, so they didn't recommend circumcision even in children with vesicoureteral reflux [17].…”
Section: Discussionmentioning
confidence: 98%
“…In patients with VUR, circumcision was more effective than antibiotic prophylaxis alone or surgical correction in preventing UTIs and the occurrence of new DMSA abnormalities [23][24][25] . Similar results were seen in boys with posterior urethral valves 26 and infants with significant antenatal hydronephrosis 27 .…”
Section: Boys With Abnormal Urinary Tractmentioning
confidence: 94%
“…Reflü cerrahisi ve koruyucu tedavi ile bu amaca ulafl›lmaya çal›fl›l›r (28). Az say›da ça-l›flmada sünnetin reflüsü olan çocuklarda ‹YE s›kl›¤›n› azaltmadaki etkisi de¤erlendirilmifltir (29,30). Cascio ve ark.…”
Section: Tart›flmaunclassified